Regulatory Issues on Raising Capital through Debentures by Public Companies in the United Kingdom - Mohammad Belayet Hossain (Sriwijaya Law Review, 2019)
Nowadays, it is common for the loans to be aggregated as a lump sum, which is then advanced to the company by the trustees. In this situation, the lenders subscribe for debenture stock, sometimes called loan stock, out of the fund. As with shares, such stock forms part of the company’s securities, which can be traded in the Stock Exchange. The lenders might require security for their loans. In this situation, a company will charge its property to secure the loan. In light of the Companies Act 2006 of the United Kingdom, this paper will analyze the various mechanisms whereby public companies raise money through debentures and the regulatory consequences of doing so. The companies legislation requires certain particulars of the charge to be registered. Therefore, this paper aims to reflect on: (a) how public companies borrow its capital through debentures or debenture stock; (b) what types of charge the public companies could issue to lenders as security; (c) how to differentiate between fixed and floating charges. This paper will also examine the question of priority among competing creditors and inconsistent decisions of the court regarding fixed and floating charges. The objectives of this paper are to: describe the meaning of ‘debenture', discuss the dispute relating granting a fixed charge over book debts, sketch the priority of charges and the statutory listing system, describe the meaning of book debts,  explain the character of and the differences between floating and fixed charges. This paper will provide recommendations that could be taken into consideration for future amendments of the Companies Act 2006.